2019
DOI: 10.1590/s0100-83582019370100014
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Harvest Desiccation in Productivity and Physiological Quality of Cowpea Seeds

Abstract: Pre-harvest desiccation is an important strategy to anticipate harvesting, preventing the seed from being left in the field in unfavorable climatic conditions. However, little is known about the use of desiccants and their application times on cowpea (Vigna unguiculata). The objective of this study was to evaluate the effect of desiccant application at different seasons and of desiccant herbicides on productivity and physiological quality of cowpea seeds. Five dessicants were evaluated: paraquat, paraquat sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…It has been applied worldwide for pre-harvest desiccation of numerous crops like wheat, soybean, cowpea, etc. (Assis et al, 2019;Malalgoda et al, 2019). Our study confirmed the efficacy of glyphosate for preharvest maize desiccation (Figures 1, 3A).…”
Section: Versatility Of Glyphosate On Cropssupporting
confidence: 84%
“…It has been applied worldwide for pre-harvest desiccation of numerous crops like wheat, soybean, cowpea, etc. (Assis et al, 2019;Malalgoda et al, 2019). Our study confirmed the efficacy of glyphosate for preharvest maize desiccation (Figures 1, 3A).…”
Section: Versatility Of Glyphosate On Cropssupporting
confidence: 84%
“…The application of paraquat favored the physiological quality of bean seeds when evaluating electrical conductivity, compared with the seeds of plants that did not receive herbicide application (Coelho et al, 2012). In evaluating the effect of application times and herbicides on the productivity and physiological quality of bean seeds, Assis et al (2019) observed that the ripening herbicides application on the plants positively affected seed vigor in the evaluation of electrical conductivity.…”
Section: Resultsmentioning
confidence: 98%
“…According to Assis et al (2019) the emergence results of seedlings in sand substrate may be considerably lower than those obtained in the laboratory germination test because, unlike the emergence test, which is conducted under sometimes unfavorable conditions. In the test of germination, the conditions of humidity, temperature, and substrate are adequate and allow expression of the maximum production potential of normal seedlings.…”
Section: Resultsmentioning
confidence: 99%
“…It has been applied worldwide for pre-harvest desiccation of numerous crops like wheat, soybean, cowpea, etc. ( Assis et al, 2019 ; Malalgoda et al, 2019 ). Our study confirmed the efficacy of glyphosate for pre-harvest maize desiccation ( Figures 1 , 3A ).…”
Section: Discussionmentioning
confidence: 99%